A novel PIGN mutation and prenatal diagnosis of inherited glycosylphosphatidylinositol deficiency. Issue 1 (30th September 2015) - Nakagawa, Taku; Taniguchi‐Ikeda, Mariko; Murakami, Yoshiko; Nakamura, Shota; Motooka, Daisuke; Emoto, Tomomi; Satake, Wataru; Nishiyama, Masahiro; Toyoshima, Daisaku; Morisada, Naoya; Takada, Satoshi; Tairaku, Shinya; et al.
Abstract : Glycosylphosphatidylinositol (GPI) anchors tether proteins to the extracellular face of eukaryotic plasma membranes. Defects in the human GPI anchor biosynthetic pathway cause inherited GPI deficiencies (IGDs) characterized by multiple congenital anomalies: dysmorphic faces, developmental delay, hypotonia, and epilepsy. We report the case of a 6‐year‐old boy with severe psychomotor developmental delay, epilepsy, and decreased granulocyte surface expression of GPI‐anchored protein that suggested autosomal recessive GPI deficiency. The case underwent target exome sequencing to screen for IGDs. Target exome sequencing of the proband identified an apparently homozygous c.808T > C (p.Ser270Pro) mutation in PIGN, a gene involved in the GPI anchor biosynthetic pathway. As his parents were expecting another child, genetic carrier screening was conducted for the parents. Direct sequencing of the parents identified a heterozygous c.808T > C PIGN mutation in the father but none in the mother. To identify the mother's mutation, we performed semi‐quantitative real‐time PCR of the PIGN exons and long PCR, identifying a microdeletion in PIGN (del exons 2–14). The proband had inherited this microdeletion from his mother. Prenatal diagnosis of the fetus revealed that it was a heterozygous carrier of the mother's pathogenic allele. Here, we report a sporadic case of inherited GPI deficiency with a PIGN mutation and the first case of prenatal diagnosis for GPI deficiency. © 2015 Wiley Periodicals, Inc.